Peritoneal Cavity is a Route for Gut-Derived Microbial Signals to Promote Autoimmunity in Non-Obese Diabetic Mice - Emani R; Alam C; Pekkala S; Zafar S; Emani MR; Hänninen A (Elsevier, 2022)
Macrophages play a crucial role in innate immune reactions, and Peritoneal Macrophages (PMs) guard the sterility of this compartment mainly against microbial threat from the gut. Type-1 Diabetes (T1D) is an autoimmune disease in which gut microbiota and gut immune system appear to contribute to disease pathogenesis. We have recently reported elevated free radical production and increased permeability of gut epithelium in non-obese diabetic (NOD) mice. Impaired barrier function could lead to bacterial leakage to the peritoneal cavity. To explore the consequences of impaired gut barrier function on extra-intestinal immune regulation, we characterized peritoneal lavage cells from young newly weaned NOD mice. We detected a rapid increase in the number of macrophages 1-2 weeks after weaning in NOD mice compared to C57BL/6 and BALB/c mice. Interestingly, this increase in macrophages was abrogated in NOD mice that were fed an anti-diabetogenic diet (ProSobee), which improves gut barrier function. Macrophages in young (5 week old) NOD mice displayed a poor TNF-α cytokine response to LPS stimulation, and high expression of Toll-like Receptor (TLR) signalling pathway negative regulator, Interleukin-1 Associated Kinase-M (IRAK-M), indicating prior in vivo exposure to TLR-4 ligand(s). Furthermore, injection of LPS intraperitoneally increased T-cell CD69 expression in pancreatic lymph node (PaLN), suggestive of T-cell activation. Leakage of bacterial components such as endotoxins into the peritoneal cavity may contribute to auto-reactive T-cell activation in the PaLN.